UPAYA PEMANFAATAN LIMBAH UNTUK MENINGKATKAN EFISIENSI PENGGUNAAN UNSUR HARA P DARI BATUAN FOSFAT ALAM PADA BUDIDAYA KEDELAI DI TANAH LIAT AKTIVITAS RENDAH(THE APPLICATION OF LIQUID WASTE TO INCREASE P NUTRIENT USE EFFICIENCYOF ROCK PHOSPHATE ON SOYBEAN CULTIVATION IN LOW ACTIVITY CLAY SOIL) - Rif’an, Muhammad; , Suwardi (Pembangunan Pedesaan, 2011)
The purpose of this study was to assess the growth and yield of white oyster mushroom on different planting medium composition and the composition of the planting medium that could generate the highest white oyster mushroom. The experiment was conducted at the home of fungi (kumbung) located in Agro Baturaden, District Baturaden, Banyumas, with altitude of approximately 325 m above sea level for 4 months (December 2009 - March 2010). The experimental design was Completely Randomized Design (CRD) with 9 treatments: 75% sawdust + 25% compost weeds; 50% sawdust + 50% compost weeds; 25% sawdust + 75% compost weeds; 75% sawdust + 25% compost dry banana leaf banana , 50% sawdust + 50% compost dry banana leaf banana, 25% sawdust + 75% compost dry banana leaf banana, 100% sawdust, 100% compost weeds and 100% compost banana dried banana leaves. Each treatment consisted of 7 baglog and took 3 baglog as samples per treatment. The variables measured were initial mycelium growth, early fruiting bodies grow, the number of fruiting bodies, clumps of fruiting bodies, the volume of fruit body, the weight of fresh mushroom, mushroom dry weight, and Biological Efficiency Ratio (BER). Based on F test and Duncan test at 5% level of error, it was found that the treatment composition 100% sawdust and dried banana leaf banana mycelium showed initial growth between 20.7 up to 26. days after inoculation or 3 days sooner. The composition of the planting medium that could produce the highest white oyster mushroom was 75% sawdust + 25% compost weeds with 171.153 g fresh weight; dry weight of 15.380 g and BER (Biological Efficiency Ratio) 24.453% and 50% sawdust + 50 % compost dry banana leaf banana with 187.230 g fresh weight, dry weight of 13.007 g and 26.747% BER.